2015
DOI: 10.1016/j.compstruct.2015.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Through-Section shear strengthening technique using steel and CFRP bars in RC beams of different percentage of existing stirrups

Abstract: The Embedded Through-Section (ETS) technique is a promising technique for the shear strengthening of\ud existing (RC) elements. According to this technique, holes are drilled through the beam section, and bars\ud of steel or FRP material are introduced into these holes and bonded to the concrete with adhesive materials.\ud An experimental program was carried out with RC T-cross section beams strengthened in shear\ud using the ETS steel bars and ETS CFRP rods. The research is focused on the evaluation of the ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 32 publications
0
55
0
Order By: Relevance
“…Khattab et al (2017) studied reinforced concrete deep beams and concluded that increasing of strips lead to an increase in beam capacity [1]. Using of FRP sheets in the strengthening of deep beams, increase beam capacity [2][3][4][5][6][7], also using of FRP bars in the strengthening of deep beams led to increasing beam capacity [8][9][10]. Another researcher studies other parameters that shall be considered in the design of deep beams [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Khattab et al (2017) studied reinforced concrete deep beams and concluded that increasing of strips lead to an increase in beam capacity [1]. Using of FRP sheets in the strengthening of deep beams, increase beam capacity [2][3][4][5][6][7], also using of FRP bars in the strengthening of deep beams led to increasing beam capacity [8][9][10]. Another researcher studies other parameters that shall be considered in the design of deep beams [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the NSM technique offers higher strengthening effectiveness than the EBR technique due to higher confinement to the CFRP composite materials provided by the surrounding concrete [2,[7][8][9]. The ETS technique has been used with considerable success for the shear strengthening of RC beams, where FRP or steel bars are installed into vertical or inclined holes drilled through the core of the beam's cross section [10].…”
Section: Introductionmentioning
confidence: 99%
“…This technique is based on the execution of holes drilled through the element cross section, in which steel or fiber reinforced polymer (FRP) bars are inserted and bonded to the surrounding concrete with an epoxy adhesive. Different FRP-2 based strengthening techniques, like Externally Bonded Reinforcement (EBR) and Near Surfaces Mounted (NSM), are being investigated and applied for the shear strengthening of RC beams; however the ETS technique was proved to be particularly efficient, providing a significant increase of shear resistance, usually higher than the one attained by using NSM and EBR techniques [1][2][3][4][5]. The ETS technique is also a cost competitive and feasible solution when EBR and NSM techniques cannot be applied [6].…”
Section: Introductionmentioning
confidence: 99%
“…Three series of beams with different percentage of existing steel stirrups were tested with the purpose of evaluating the influence of the internal shear reinforcing ratio, as well as the influence of the percentage and inclination of the ETS bars on the strengthening effectiveness. A detailed description of the experimental program and the discussion of the results are presented in Breveglieri et al [4,5].…”
Section: Introductionmentioning
confidence: 99%